Structural and electronic-structure investigations of defects in Cu-ion-implanted SnO2 thin films. (September 2020) - Chaudhary, Surekha; Saraswat, Himani; Devi, Devarani; Kulriya, Pawan; Singh, Fouran; Won, Sung-Ok; Shin, Hyun-Joon; Parkash, Jai; Sharma, Aditya
Abstract: SnO2 thin films have been deposited on Si substrates using RF-magnetron sputtering and implanted by 200 keV Cu − ions with ion fluence of 2.79 × 10 16 ion/cm 2 and 4 × 10 16 ion/cm 2 . Post annealing is done on the pristine and Cu − ion-implanted SnO2 thin films. Samples were characterized using the grazing-incidence X-ray diffraction (GIXRD), field-emission scanning electron microscopy (FESEM) and near-edge X-ray absorption fine structure (NEXAFS). After the annealing, amorphous to crystalline phase transition and growth of particles are seen. It is also evidenced that Cu ions do not make metallic/oxide phases up to the implantation dose of 2.79 × 10 16 ion/cm 2 . Cu L-edge NEXAFS has confirmed the Cu 2+ ions in the samples. The O K-edge NEXAFS spectra of annealed films have shown diminished peak intensity of O 2p to Sn 5s hybridized orbitals which signify the O vacancy formation. A pre-edge peak in the O K-edge NEXAFS of Cu implanted films has evolved and confirms the additional hybridization of unoccupied Cu d orbitals with O 2p orbitals. The improved intensity of Sn M5, 4 -edge features is due to the enhanced crystallinity in annealed samples. Ion-solid interaction induced structural and electronic structure amendments are briefly discussed in the light of energy-loss mechanism. Highlights: SnO2 films were deposited on Si substrates using RF-sputtering technique. Ion implantation was done using Cu ions with ion fluence 2.79 × 10 16 ion/cm 2 and 4 × 10 16 ion/cm 2 . Amorphous to crystalline phase change, grain growth and release of strain is studied by GIXRD. O vacancy formation is confirmed by O K-edge NEXAFS. Additional hybridization of unoccupied Cu d orbitals with O 2p orbitals is also studied.